Thermoelectrics and its energy harvesting. - Rowe, David Michael (CRC Press, 2012)
With contributions from leading experts, this book begins with an overview of thermoelectric nanotechnology, setting the scene for the topics covered in the rest of the volume. It provides a comprehensive review of the progress made in the development of modules and their application in devices. The book highlights dramatic advances in miniaturization and its successful commercialization in energy harvesting. It then covers thermoelectric energy harvesting and contains reviews of the solar, automotive, and medical harvesting of waste heat.